Long-term impact of early non-infectious complications at the initiation of peritoneal dialysis. Issue 1 (January 2023) - Chan, R; Walker, RJ; Samaranayaka, A; Schollum, JBW
Background: Early non-infectious complications at initiation of peritoneal dialysis (PD) are a major burden with unknown long-term impacts on individuals. Methods: Prospective multicentre cohort study using univariable and multivariable Cox regression to identity mortality risk and PD discontinuation risk in those with and without non-infectious complications. All individuals commencing PD between 1 January 2014 and 31 December 2018, registered in the New Zealand Peritoneal Dialysis Registry (NZPDR) were followed up to 31 December 2020. Early non-infectious complications defined as functional, catheter-related, exit-site dialysate leak or anatomical leak complications occurring within 30 days of initiation of PD. Primary outcomes were patient survival and time on PD therapy. Secondary outcomes were peritonitis free survival, first PD catheter survival and catheter tunnel infection free survival. Results: Of 1596 individuals included in the study, 102 experienced an early non-infectious complication. Multivariable analysis demonstrated these complications were associated with higher risk of overall mortality (hazard ratio (HR) 1.71; 95% confidence interval (CI) 1.21–2.44), PD discontinuation (HR 1.84; 95% CI 1.41–2.41) and first catheter failure (HR 2.89; 95% CI 2.28–3.66). No difference was found for risk of development of first peritonitis episode or catheter tunnel infection. Mortality risk was associated with functional and exit-site dialysate leak complications and continued beyond 180 days. Risk of PD discontinuation and first catheter loss were associated with catheter and functional complications in the first 180 days. Conclusion: Early non-infectious complications are associated with long-term mortality risk. Further research in risk factors and causes of early non-infectious complications are required.